International economic sanctions and third-country effects - Fabio Ghironi; Daisoon Kim; G. Kemal Ozhan (Bank of Canada, 2023)
This paper studies international trade and macroeconomic dynamics triggered by economic sanctions, and the associated welfare losses, in a calibrated, three-country model of the world economy. We assume that there are two production sectors in each country, and the sanctioned country has a comparative advantage in production of a commodity (for convenience, gas) needed to produce final, differentiated consumption goods. We consider three types of sanctions: sanctions on trade in final goods, financial sanctions, and gas trade sanctions. We calibrate the model to an aggregate of countries currently imposing sanctions on Russia (the European Union, the United Kingdom, and the United States), Russia, and an aggregate of third countries (China, India, and Turkey). We show that, instead of reflecting the success of sanctions, exchange rate movements reflect the type of sanctions and the direction of the resulting within-country sectoral reallocations. Our welfare analysis demonstrates that the sanctioned country's welfare losses are significantly mitigated, and the sanctioning country's losses are amplified, if the third country does not join the sanctions, but the third country benefits from not joining. These findings highlight the necessity, but also the challenge, of coordinating sanctions internationally.
Keywords: F31; F41; F42; F51; 330; Economic models; Exchange rates; International topics